Historiography in Samanid’s Period - Maryam Doalatraftar Haghighi; Mohammad Sepehri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The works written in Samanid’s period in the field of history are partly the continuation of simple writing in the late second century A.H. The prose by a number of historians in the Samanid Period is artifact and the authors just tried to praise the ruler’s emirs and ministers exaggeratedly. They counted them as the right kings of time. Historiography in this period was mostly based on personal observation, and for this reason access to the documents belonging to this period is very important. The main questions of this research are as follows: what are the essential features of historiography in the Samanid’s Period? What are the strengths and weaknesses of the best historical sources in this Period? This research explains the strong and weak points of historiography in the Samanid’s Period and also tries to identify the main features of historical sources within this era. Among the important features of Islamic historiography in this Period, the cultural and civilizational attitude of historians, holistic historiography, the appearance of rationalist analytical and educational attitude, combining various sciences such as History, Geography, Astronomy, and knowledge about different science and fields can be mentioned. Some other things that we can see in the historical compilations of this period are: starting to translate (Balamy historiography), avoiding the methods of news compilation based on the principles and traditions of Hadith records and also the appearance of new methods of historiography (local history like history of Bokhara). In general, the boom of historiography and the appearance of some important historical works in the period of Samanid are achieved through a variety of factors in the realm of this Iranian Family.